Annular variable-spacing fin arrangement in latent heat storage system. (June 2022) - Zhu, Yuxi; Qiu, Yan
Abstract: In present research, a new annular fin arrangement with variable fin spacing is designed to enhance the heat transfer in melting and solidification processes. The enthalpy-porosity technique is used to study the heat transfer and phase change process of the transient model. The results are mainly analyzed from the aspect of melting/solidification time, heat storage/release capacity and Nusselt number. Taking the uniform finned structure as base case (b-case), combined with heat storage/release increment and heat storage/release time reduction, the concept of growth rate is proposed. The numerical results show the overall thermal performance is improved by increasing the density of fins at the top and bottom ends and moving fins to the ends in the melting process, and the growth rate can reach to 26.79%. Yet the solidification process cannot be improved just by the methods and the maximum growth rate is just 4.79%. Therefore, three-time modification is proposed for improving solidification process by arranging fins evenly in the middle and densely at the top and bottom ends. The proposed structures show superior thermal performance in melting and solidification processes. The solidification time in the structure can be reduced by 18.94% compared with b-case, and the growth rate can be up to 15.78%. Meanwhile, the growth rate in melting process further reaches to 30.46%. The Nusselt number is increased by 55.65% and 16.14% in melting and solidification process by the three methods. Additionally, the correlation equations are developed using the dimensionless parameters to predict the total melting time and average Nusselt number. Highlights: The novel fin arrangements were proposed for improving the heat transfer in both melting and solidification processes. Correlation equations were developed to predict the total melting time and average Nusselt number for the novel fin arrangements. The heat transfer was enhanced in melting and solidification process by arranging fins evenly in the middle and densely in the ends compared to uniform fin arrangement. The thermal performance of the latent heat storage systems was evaluated by a new parameter named growth rate.